Occupational Exposure to Solar Radiation and the Eye: A Call to Implement Health Surveillance of Outdoor Workers - Modenese, Alberto; Chou, B. Ralph; Ádám, Balázs; Loney, Tom; Silva Paulo, Marilia; Tenkate, Thomas; Gobba, Fabriziomaria (La Medicina del Lavoro, 2023)
Globally, hundreds of millions of outdoor workers are exposed to solar radiation (SR) for the majority of their working life. Such occupational exposure is known to induce various adverse health effects to the eyes, mainly related to its ultraviolet (UV) component. The present work is a call-to-action aimed at raising the awareness on the need of health surveillance for the prevention of the chronic ocular diseases in outdoor workers. Photo-chemical chronic damage can induce pterygium at the outer layer of the eye and cataract in the lens. Considering carcinogenic effects, rare squamous-cells tumors of the cornea and/or of the conjunctiva and the ocular melanomas are associated with UV radiation exposure. Solar UV-related eye diseases should be considered as "occupational diseases" when there is sufficient exposure in workers, but they are often not recognized, and/or frequently not reported to the national compensation authorities. Therefore, to prevent the burden of these work-related eye pathologies, an adequate risk assessment with identification of appropriate preventive measures, and a provision of periodic health surveillance to the exposed workers, in particular considering those at higher risk of exposure or with individual susceptibility, should be urgently implemented.